Effects of Behavioural Uncertainties In Property Valuation (International Journal of Built Environment and Sustainability, 2020)
Psychological and behavioural dimensions play a vital role in influencing Valuers’ valuation judgements, thus affecting the validity, accuracy and discrepancy (reliability) of property values. However, behavioural uncertainty research, specifically within the discipline of property valuation among property Valuers, is still limited, particularly in developing countries with their unique property valuation systems, and has been so far conducted in an independent, separate manner, which looks into the behavioural uncertainties non-connectedly. Therefore, this study aims to examine the behavioural uncertainties of local Valuers in property valuation, vitally addressing the questions of behaviours involved and how a behavioural uncertainty is associated with other behavioural issues. This study adopted a phenomenological design, where a session of focus group discussions with 10 public-private Valuers from Johor Bahru, Malaysia was conducted. Results show that local Valuers were subject to various, simultaneous interwoven behavioural uncertainties, which ultimately form a behavioural framework of associations, including biases, client influences, heuristics, professional ethics, and opportunistic behaviours in making their valuation judgement. Biases (subjective preference) and professional ethics (negligence and carelessness) are the two most dominant behaviours involved in local property valuation. These findings provide policy insights to both public and private Valuers, academicians, and the market about the importance of understanding behavioural property economics, that crucially enables them to collectively create a sustainable property valuation environment.
Keywords: Behavioural Uncertainties; Property Valuation; Valuation Judgement; Behavioural Economics; Validity and Accuracy; Johor Bahru; Malaysia